Development Of Carbon And Potassium-Incorporated Titanium Dioxide Nanotube Arrays For Solar Energy Harvesting Applications - Krengvirat, Warapong (2013)
TiO2 nanotube arrays have attracted great interest as the most promising candidate for solar energy harvesting applications. However, poor visible-light absorption and high recombination of charge carriers still remain as challenging issues for their practical applications. Hence, the objective of this work was to develop carbon and potassium-incorporated TiO2 nanotube arrays for solar energy harvesting applications, including photodecolorization, photoelectrochemical cell (PEC) and dye-sensitized solar cells (DSSC). Visible-light responsive TiO2 nanotube arrays were rapidly grown with a rate of ~289 nm min-1 by anodic oxidation in ethylene glycol (EG) containing 0.5 wt% ammonium fluoride (NH4F) and 1 wt% H2O. The presence of adsorbed-carbonate species and interstitial carbon in TiO2 nanotubes originated from the pyrogenation of EG resulted in the generation of localized state, and thus enabled the visible-light absorption. Anatase TiO2 nanotube arrays with high surface area (110.9 m2 g-1) were obtained by facile immersion of as-anodized nanotube arrays in hot water at ~90C. Such hot water-treated nanotube arrays exhibited efficient visible-light photodegradation of methylene blue with the decomposition rate of ~11 % h-1. This value is relatively higher than heat-treated arrays (~9 % h-1) and P25 powder (~2 % h-1). However, heat treatment at 400C for 4 h was found as essential approach to obtain better crystallinity for high PEC and DSSC properties. Heat-treated TiO2 nanotube arrays with average nanotube lengths xxxiv of 18 m, thick walls (13 nm) and large pore sizes (115 nm), with high aspect ratio (~123.6) exhibited remarkable ability to generate H2 at a rate of ~508.3 L min-1 cm-2 and photoconversion efficiency () of ~2.3%. The growth of TiO2 nanotube arrays and their electrochemical properties were further improved by simple addition of potassium hydroxide (KOH) into fluorinated-EG. The incorporation of 1 wt% of 1.0 M KOH facilitated an equilibrium growth of nanotube arrays with a rate of ~353 nm min-1. The adsorbed-potassium species further extended the light visible-light absorption to 780 nm. Furthermore, the electron donation nature of adsorbed-potassium promoted larger number of charge carriers (9.7 × 1021 cm-3). Carbon and potassium-incorporated TiO2 nanotube arrays with aspect ratio of 140.5 exhibited superior photoelectrochemical H2 generation with an evolution rate of ~658.3 L min-1 cm-2 and  of ~2.5%, which is 30 % higher than that of without potassium. Carbon and potassium-incorporated TiO2 nanotube arrays were assembled to back-side illumination DSSCs using N719 dye and iodide/triodide redox electrolyte. Well-aligned nanotubes with average nanotube lengths of 18 m, thick walls (13 nm), and large pore sizes (130 nm) allowed a greater penetration of excited h and ease charge carrier diffusion. Furthermore, high geometric surface area up to 755 could harvest higher dye adsorption. A maximum  of 2.78% was achieved from a 17.8 m length TiO2 nanotube arrays, with open circuit potential of 0.67V, current density of 8.95 mA cm-2, and filled factor of 46.39%.